Optimization of flaxseed milk fermentation for the production of functional peptides and estimation of their bioactivities - Sharma, Poorva (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2021)
Bioactive peptides are protein fragments which have a positive impact on the functions and conditions of living organisms. Apart from other animal and plant sources flaxseed is an excellent source of bioactive peptides. In recent years, fermentation has been explored as effective way for bioactive peptides generation. Hence, the present study has been carried out to evaluate an indigenous Lactobacillus plantarum strain NCDC 374 for fermentation and peptides generation in flaxseed milk. Optimization of fermentation condition to obtain maximum functional properties (Proteolytic activity, Antioxidant activity and ACE inhibition %) was investigated using response surface methodology. Optimal condition to produce the functional peptides were found to be 4.20% inoculum size with 126 hours of fermentation time. The fermented milk resulted in 67.38% inhibition in DPPH, 41.35% inhibition in ACE and 30.38 micro gram leucine/ml proteolytic activity. Molecular weight cut off membrane (Viva spin) were used to fractionate the peptides. 10 kDa peptides showed optimal results for % DPPH inhibition, ACE inhibition, Antimicrobial activity and DPP-IV inhibition as compared to 5 kDa